(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Curriculum planning is one of the most important components of the teaching methodology used in foreign languages. Pedagogy and course planning are distinctive and peculiar because language learning is cognitive. This document focuses on the aspects and challenges of the curriculum strategy and the design of the Spanish language in particular. The modules must be precise and call the attention of the student. As the Spanish language is easier to learn, students are generally attracted to learning this language. However, Spanish grammar can be complex at times and, therefore, more emphasis can be placed on communicative learning. The Spanish curriculum can be delineated in such a way that the learning includes both the direct method and the grammatical translation method. The teaching method has a vital role in the planning of the course, which will be analyzed in this document. However, techniques and pedagogies may differ since students may have different requirements. In addition, the academy involved in curriculum planning needs to take into account many factors, such as the age of the students, their mother tongue and their cognitive capacity. This study will be an inspection on the various elements and tools needed to plan, write and assemble the curriculum of the Spanish course.